Dampak Penggunaan Artificial Intelligence (AI) dalam Meningkatkan Kompetensi Akademik Mahasiswa Prodi PAI Pascasarjana UIN Syahada Padangsidimpuan - Sangkot Hayati; Zulhammi Zulhammi; Lelya Hilda (Universitas Islam Negeri Sumatera Utara Medan, 2025)
AbstractThis study aims to describe the form of utilization of Artificial Intelligence (AI), especially those based on Natural Language Processing (NLP), in the learning process and analyze its impact on the academic competence of students of the Postgraduate Islamic Religious Education Study Program, Masters Program, UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan. In addition, this study also identifies various supporting and inhibiting factors in the application of AI as a learning medium in higher education environments. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through in-depth interviews, observations, and documentation. Data were analyzed qualitatively through the process of data reduction, data presentation, and drawing conclusions. The results of the study showed that students utilized NLP-based AI, to access academic literature and information, assist in compiling scientific papers, improve understanding of the material, and as a companion media in the independent learning process. The use of AI has a positive impact on several aspects of students' academic competence, including increasing digital literacy, strengthening scientific thinking skills, effectiveness in completing academic assignments, and independence and responsibility in learning. Supporting factors for the use of AI in learning include user readiness as reflected in the mastery of digital technology, the availability of internet access, and institutional support such as adequate training and facilities. Meanwhile, inhibiting factors include a weak understanding of the ethics of using AI, the risk of plagiarism, and the potential for dependence on technology that can reduce students' critical thinking.